(untitled) (Research, Society and Development, 2023)
The aim of this study was to evaluate the possible anxiolytic effect of the ethanolic extract of Citrus aurantium L. leaves on experimental models sensitive to anxiolytic drugs. The mice were divided into three groups (test, positive control, negative control) for administration of the ethanolic extract of Citrus aurantium L. leaves, diazepam and vehicle. To assess motor activity in mice (spontaneous activity), the Open Field and Hide the Spheres tests were carried out. The experimental values obtained are expressed as mean ± standard error of the mean (SEM) and statistical analysis was carried out using the Kruskal-Wallis test, followed by Dunn’s multiple comparison test and spectrophotometry to identify the main compounds present in EECAL. The results showed that for the group of animals treated with EECAL (500mg/kg), there was a significant reduction (p<0.05) in exploratory capacity of 66.4±6% compared to the negative control (NC), when the three times were compared cumulatively. The data from the evaluation of animal compulsivity in the ball-hiding model showed that EECAL (500mg/kg) significantly (p<0.05) reduced apparent compulsion by 79.2±0.3% when compared to the negative control (NC). Thus, based on the analyses carried out, it can be concluded that the ethanolic extract of Citrus aurantium L. has a significant anxiolytic effect, as well as a decrease in spontaneous motor activity, indicating a possible profile of effects similar to benzodiazepines with probable CNS depression.